Harmonization & Conflict - Antonia Ayutriana; Aurelia Yofita; Desvina Gita Resna; Eri Yanti Nopi Eling; Galuh Intan; Maria Fransiska Apriyani; Yuniar Anggraini; Yustinus Jacob E. F; Zenifer Kristianita Tarigas; Jagad Aditya Dewantara (CV. Rayyan Dwi Bharata, 2023)
There are many things that made us interested in this book where the book discusses a lot about the conflicts that exist on campus with the community, from this we can learn and also respond as students or the campus knows how to solve problems or solutions. which exists. The conflict incidents in this book can give us practice to prevent this from happening in the future and on other campuses. The theories provided in the studies can also be a source of reference for us as students. In the first chapter of this book, it discusses a university that has many agents of change, there are lecturers as educators or researchers, there are students who are always making changes in thinking and trying new methods and lifestyles, there are administrative and technical staff who have specific managerial and technical skills in supporting the teaching and learning process and managing the entire campus area. Small conflicts have continued to occur throughout the history of the development of this campus. The nuances of conflict between the Unimal campus community and the surrounding gampong community are actually an extension of the vertical and horizontal conflicts that have existed in Aceh for a long time, between the government (central and regional) and the Free Aceh Movement. It is the main discussion in this book. Like the conflict between the residents of the gampong around the campus and Unimal, it has been ongoing and intertwined with the wider conflict, the Aceh conflict which has been going on for quite a long time since 1953 which has put Aceh into a territory that is rebelling against the Central Government. This peace agreement became the initial capital for creating new socio-political conditions in post-conflict Aceh and as a prerequisite for carrying out rehabilitation and reconstruction activities for the area after being hit by the tsunami disaster on December 26, 2004. Several stages in the peace process were successfully passed with generally quite positive results. even unexpectedly; demobilizing GAM and decommissioning its weapons; non-organic redeployment of TNI/POLRI; amnesty for GAM political prisoners; reintegration of former GAM members; the enactment of Law Number 11 of 2006 concerning the Government of Aceh; and the election of the head of the Aceh administration and local elections at the district and city levels throughout Aceh.